Tourism Village Management and Development Process: Case Study of Bandung Tourism Village - Muhammad Henfi Abdul Khoir; Ahmad Rimba Dirgantara (ASEAN Journal on Hospitality and Tourism, 2020)
Tourism village destinations are built and opened in addition to increasing the income of local communities and local governments as well as providing a new atmosphere for local and foreign tourists. The Local Government's program to develop tourism villages in Bandung Regency continues to be pursued, but the current managers are faced with managerial ability to manage tourism villages properly by tourism village management standards. This raises research questions about how to develop a management and development village tourism module that applies to village tourism managers to preserve the environment and to elevate the local potential based on local wisdom. This research uses the case study method. The analysis used is descriptive qualitative analysis. The results of the study recommend 12 topics of learning modules for the management and development of tourism villages which are expected to be able to help tourism village managers to manage their tourism villages well and sustainably. The learning modules are tourism village management, event management, customer satisfaction management, accommodation management, food and beverage management, handicraft management, marketing management, customer behavior, contemporary marketing, human resource management, conflict management, and tourism policy.